NOISE LEVEL OF TRANSPORTATION IN BANDA ACEH CITY - Wahab, Abdul (Jurnal Pendidikan Geografi Gea, 2018)
The aim of this research is to know the noise level due to transportation activity in Banda Aceh. This research was conducted in three locations, namely Simpang Lima, Simpang Surabaya, and Jl. Mohd. Jam. Data collection time during rush hour is morning, noon and afternoon. Data retrieval using the Sound Level Meter tool with a time span of 1 hour each time the recording. Each data listed on the tool is recorded every 5 seconds for 1 hour so that the average of each measurement is obtained. At Simpang Lima 74.12 dB (A) morning, 71.4 dB (A) noon and 77.14 dB (A) afternoon. In Simpang Surabaya 75.37 dB (A) morning, 75.19 db (A) noon and 76.08 dB (A) afternoon. The last location is on Jl. Mohd. Jam is 71.89 dB (A) morning, 71.74 dB (A) noon and 75.67 dB (A) afternoon. The results showed that noise increased in the afternoon and average noise above 70 dB (A). These findings indicate that the noise level in Banda Aceh has exceeded the threshold set by the government.